Weighted Energy Efficient Cluster Based Algorithm in MANET (International Journal of Engineering and Computer Science, 2017)
A mobile adhoc network is a network in which nodes are dynamic in nature and has limited bandwidth and minimum battery power. For providing the scalable routing the nodes are divided into clusters, in clusters there should be a cluster head which contains all the information about its nodes, as in the flat routing every node perform the same role therefore network lifetime is less. The different schemes in clustering are based on different criteria. A cluster head is selected according to specific combination or metric such as identity, degree, energy, weight, mobility etc. Here, a new algorithm is proposed based on the existing algorithm “A novel weight based clustering algorithm for routing in MANET” the energy factor is included in the selection of cluster head. If the two nodes in the cluster are the candidates for the selection of cluster head then the energy of every node is calculated to select appropriate cluster head. This algorithm is named as “weighted energy efficient cluster based algorithm”. The results of this algorithm are compared with the existing one. The results are calculated on four parameters. These are end to end delay, packet delivery ratio, energy and throughput. The throughput of the newly proposed algorithm is better than the existing WBA algorithm. And the other factors are compared which shows high rate of WBA algorithm